Toddler Sleep Challenges: All in a Day's Work. Issue 9 (December 2019) - Barnes, Andrew J.; Kroupina, Maria; Perry, Nicole; Augustyn, Marilyn
Abstract : CASE: Leo is a 26-month-old boy who you are seeing for an urgent care visit due to "sleep difficulty, " particularly sleep onset. Since age 1, he screams, hits, and kicks his mother every day, starting after she gets home from work at 5 PM (or before the family's dinnertime on her days off) and escalating over the course of the evening until he "wears himself out" and falls asleep in a crib in his own room around 9 to 10 PM Once asleep, he sleeps well through the night and wakes easily around 7 AM in a pleasant mood; his mother leaves for work soon after he awakens. He naps after lunch for 2 to 3 hours on weekdays at an in-home child care with 1 to 2 adult caregivers and 5 other children aged 0 to 5 years. He refuses to nap at home. Leo goes to bed easily when his father puts him to bed if his mother is not at home, but his mother feels that evenings are the only time she can spend with Leo, and so, she tries to put him to bed most nights. However, because of Leo's behaviors at bedtime with her, she feels inadequate, depressed, and guilty; when she tries to disengage or allow her husband to help, Leo screams, "Mommy, mommy!" and tries to gain access to her and resists his father putting him to bed until his mother returns. Both parents worry that "he would not grow out of this, " and his mother now avoids coming home from work for fear of Leo's behavior. Both parents feel that this situation is causing marital strain. Leo was born healthy at full-term and is an only child; pregnancy was complicated by hyperemesis gravidarum. Leo has been healthy and meeting developmental milestones. His parents describe his temperament as "like his father at that age, " "easy, but never able to self-soothe, " "intense" in his emotional reactions, persistent, "strong-willed and serious, " and "shy and observant, withdrawn at first and then getting more pleasant after a while" in novel situations. Behaviorally, he engaged in noninjurious head-banging at home when upset between 12 and 15 months; bit children a few times at child care between 20 and 24 months; and lately refuses to share or will push other children at child care every few weeks. His parents recently read a book about parenting "spirited" children but did not find it helpful. What would you do next?